1987
DOI: 10.1007/bf00544562
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of an aqueous solution of a new synthetic somatostatin analogue administered to man by gavage

Abstract: To determine the local gastrointestinal absorption of a new synthetic somatostatin analogue (SMS 201-995 = Sandostatin), an intestinal tube was passed in eight healthy volunteers and on different days an aqueous solution was administered at four different locations: stomach, proximal duodenum, ligament of Treitz and jejunum. In a follow-up study, an oro-ileal tube was passed in six of the original volunteers and the drug solution was administered in to the terminal ileum. The aqueous solution of SMS was rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…Direct competitive enzyme immunoassay (EIA), as a result of its superior sensitivity, was used to quantify the presence of vapreotide in the receptor compartment. This competitive binding assay is based on the relative affinity of (1) the vapreotide (in the sample) and (2) an enzymatic tracer prepared by covalent coupling of vapreotide to an enzyme (acetylcholinesterase), to antivapreotide antibodies. The quantification limit corresponded to 100 pg/ml.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct competitive enzyme immunoassay (EIA), as a result of its superior sensitivity, was used to quantify the presence of vapreotide in the receptor compartment. This competitive binding assay is based on the relative affinity of (1) the vapreotide (in the sample) and (2) an enzymatic tracer prepared by covalent coupling of vapreotide to an enzyme (acetylcholinesterase), to antivapreotide antibodies. The quantification limit corresponded to 100 pg/ml.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…In an attempt to avoid the parenteral route, more convenient Bpatient-friendly^routes of drug delivery have been investigated. The results have been mixed: orally administered octreotide (another somatostatin analogue commercialized as Sandostatin \ ) is hampered by a relatively low bioavailability (2) and because of poor local tolerability, nasal administration is also inconvenient (3). The transdermal route is an attractive alternative to deliver therapeutic drugs (4).…”
Section: Introductionmentioning
confidence: 99%
“…When given orally, only 30% of the dose is absorbed (Beveridge et al, 1981;Frey et al, 1988;Ptachinski et al, 1986). Compared with other peptide drugs, however, the extent of absorption is high (Kohler et al, 1987). Nevertheless, the absorption of cyclosporin is very variable and is affected by physiological and pharmaceutical factors such as bile (Mehta et al, 1988;Venkatamaranan et al, 1985), food (Gupta & Benet, 1990;Keown et al, 1982;Ptachinski et al, 1985), and vehicle (Johnston et al, 1986) resulting in high inter-and intrasubject variability of pharmacokinetic parameters (Lindholm et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It is used clinically in the therapy of acromegaly and in the symptomatic treatment of carcinoid syndrome or endocrine tumours of the GI tract (Del Pozo, 1988;Battershill & Clissold, 1989). Recent studies in healthy volunteers have demonstrated that octreotide effectively suppresses plasma insulin levels after oral administration, indicating that functionally active peptide is absorbed (Williams et al, 1986;Fuessl et al, 1987), despite its rather low systemic bioavailability of about 0.3% (Kohler et al, 1987). It is not known, whether this low bioavailability is due to restricted absorption sites in the intestinal tract, where the drug passes by, or due to an interaction with intestinal content such as biliary or pancreatic fluids.…”
Section: Introductionmentioning
confidence: 99%